2002
DOI: 10.1111/1468-0009.00009
|View full text |Cite
|
Sign up to set email alerts
|

Disability as a Public Health Issue: Findings and Reflections from the Massachusetts Survey of Secondary Conditions

Abstract: In the last decade, the health status of individuals with disabilities has emerged as an explicit focus of public health attention, with consumers, policymakers, and researchers joining in defining and implementing an agenda in this area. With small federal grants from a few agencies, the field has begun to produce research findings, academic curricula, and model policies and interventions to promote health and prevent adverse outcomes among people with disabilities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 16 publications
2
56
0
Order By: Relevance
“…Finally, and perhaps most importantly, we found that just over half of adults with disabilities and SPD were receiving medical care for a mental health condition. Our finding that disability is associated significantly with SPD is consistent with scientific literature showing that depressive disorders are among the most prevalent and serious secondary conditions related to disability, [19][20][21][22][23][24][25][26][27] and indeed, they may also be the primary health condition. 24 One large cross-sectional study found the prevalence of SPD highest among Los Angeles County, CA adults reporting disabilities compared to the general adult population (28 % vs. 5 %).…”
Section: Discussionsupporting
confidence: 90%
“…Finally, and perhaps most importantly, we found that just over half of adults with disabilities and SPD were receiving medical care for a mental health condition. Our finding that disability is associated significantly with SPD is consistent with scientific literature showing that depressive disorders are among the most prevalent and serious secondary conditions related to disability, [19][20][21][22][23][24][25][26][27] and indeed, they may also be the primary health condition. 24 One large cross-sectional study found the prevalence of SPD highest among Los Angeles County, CA adults reporting disabilities compared to the general adult population (28 % vs. 5 %).…”
Section: Discussionsupporting
confidence: 90%
“…These types of items may inflate scores when used with people who are in poor health or aging or who have a disability. Scores are used to generate the following diagnoses: nondepressed [0-5], clinically significant symptomatology [6][7][8][9][10], and probable major depression [11][12][13][14][15][16][17][18][19][20][21][22]. The test developers (41) found a test-retest coefficient of 0.87 (P , 0.001), and for the full scale, the standardized-item alpha was 0.93 (P , 0.001).…”
Section: Methodsmentioning
confidence: 99%
“…Because secondary conditions are common in persons with disabilities (4)(5)(6)(7)(8), persons with severe SCI are more vulnerable to developing them (9,10) Anson and Shepherd (11) reported patterns of secondary complications among 348 outpatients evaluated by a clinical team. Approximately 95% had at least 1 secondary condition and 58% had 3 or more, with the most prevalent being pain (45%), overweight or obesity (40%), spasticity in patients with cervical or thoracic injuries (74%), urinary tract infections (27.2%), and pressure ulcers (22.4%).…”
Section: Introductionmentioning
confidence: 99%
“…Research with PWDs has linked substance abuse with increases in rates of secondary disabling conditions, substantial decreases in employment rates, increases in poverty rates, and delays in adjustment to acquired disability (Drubach et al, 1993;McKinley et al, 1999;Taylor et al, 2003;Wilber et al, 2002). In addition, PWDs who drink heavily or use drugs are more likely to be victims of crimes such as rape, assault, and robbery; to be involved in accidents; and to have a variety of substance-use-related health and social problems when compared with abstaining PWDs (Burgard et al, 2000;Kolakowsky-Hayner et al, 2002;Moore & Li, 1994;Moore & Polsgrove, 1991).…”
Section: Introductionmentioning
confidence: 99%